The unsteady free convection flow of rotating second grade fluid over an oscillating vertical plate - Mohamad, A. Q. (Penerbit UTM Press, 2016)
In this paper, the exact solutions for unsteady free convection flow of rotating second grade fluid over an isothermal oscillating vertical plate are investigated. This phenomenon is modeled in the form of partial differential equations with initial and boundary conditions. Some suitable non dimensional variables are introduced. The corresponding nondimensional equations with conditions are solved using Laplace transform technique. Exact solutions for velocity and energy profiles are obtained. They are expressed in simple forms in terms of exponential and complementary error functions of Gauss. It is found that they satisfy governing equations and conditions imposed. Computations are carried out and the results are analyzed for various emerging parameters.